FAKTOR-FAKTOR YANG MEMPENGARUHI IBU HAMIL TERHADAP PERILAKU VOLUNTARY COUNCELLING TEST (VCT) - Agustin Setianingsih; Nur Khafidhoh (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
HIV cases from 390,000 young children less than 15 years were newly infected with HIV, 90% was a result of contracting through the mother to the baby. Distribution of HIV cases in 2011-2013 the highest in the district of North Semarang. The sub-district health centers Bandarharjo active by doing VCT, but pregnant women who do VCT only about 10% of from total pregnant women. The purpose of this study was to determine the factors that influence the behavior of pregnant women Voluntary Counseling And Test (VCT) in the sub-district health centers Bandarharjo North Semarang, Semarang. This research is an explanatory research with cross sectional method. Data collection techniques with interviews using a structured questionnaire. The population of this study were pregnant women in health centers Bandarharjo which is 45 pregnant woman. Sampling method with total sampling technique. The results showed 82.2% of pregnant women in the sub-district health centers Bandarhardjo not VCT. Variables that are not related is Pregnancy Awareness Level of HIV / AIDS and VCT (p = 0.272 0.05) and Maternal attitudes about HIV / AIDS and VCT (p = 1.000 0.05). Characteristics of pregnant women were age 80.0 % of healthy reproductive age ( 20-35 years ) , 48.9 % secondary education , occupation housewife 46.7 % , 62.2 % husbands job working as an employee. Suggestion: For health professionals, especially midwives should do counseling asks respondents to disseminate to other friends about HIV /AIDS and VCT. For the Department of Health: Designing and implementing promotional execution prevention of transmission of HIV/ AIDS from mother to child transmission (PMTCT) and VCT counseling training.